Torsional stiffness bounds of helical structures under the influence of kinematic constraints. (August 2015) - Karathanasopoulos, Nikolaos
Abstract: The current work provides a framework for the assessment of the mechanical response bounds of multilayer helical assemblies. To that extent, the effect of structural kinematic constraints is analyzed, considering a wide range of braiding patterns for the helical assembly. Thereupon, torsional response bounds are retrieved, introducing scaling factors that relate the stiffness properties of the kinematically constrained structure to analytical, closed-form expressions.